AN OLD FRIEND REVISITS: CHLORAMPHENICOL OPTIC NEUROPATHY. (29th November 2012) - Wong, SH; Silva, F; Hove, M; Acheson, JF; Plant, GT
Abstract : A 66-year-old woman presented in October 2011 with bilateral visual failure of subacute onset. She has Rheumatoid Arthritis, treated with methotrexate (since 2002), etanercept (2003–2009). A right knee replacement was revised and underwent 6 washouts for persistent infection. Antibiotics included vancomycin, amoxicillin, and daptomycin. Chloramphenicol 4 g daily was started in June 2011 (14 weeks before visual loss). 10 days after onset of visual loss she had visual acuity of 3/24 (Snellen) bilaterally, hyperaemic optic discs and centrocaecal scotomas. The control Ishihara plate could not be read. Toxic optic neuropathy secondary to chloramphenicol was suspected; chloramphenicol had been stopped on Day 6 of visual symptoms. 4 weeks after stopping chloramphenicol acuity was 6/5 (right), 6/6 (left) and visual fields normal, but Ishihara colour plates impaired at 8/13 bilaterally. At the onset of visual symptoms she developed paraesthesiae of limbs which also improved. Examination showed L5 dermatomal loss to pinprick and abnormal proprioception at the toes. From 1950 to 1988 approximately 40 cases of chloramphenicol optic neuropathy were reported, but only two in the past 12 years. This case highlights the potential pitfalls of older generation antibiotics and unfamiliar adverse effects. This may become more pertinent as antibiotic resistance increase.